2014
DOI: 10.1128/iai.02284-14
|View full text |Cite
|
Sign up to set email alerts
|

Rat Indwelling Urinary Catheter Model of Candida albicans Biofilm Infection

Abstract: Indwelling urinary catheters are commonly used in the management of hospitalized patients. Candida can adhere to the device surface and propagate as a biofilm. These Candida biofilm communities differ from free-floating Candida, exhibiting high tolerance to antifungal therapy. The significance of catheter-associated candiduria is often unclear, and treatment may be problematic considering the biofilm drug-resistant phenotype. Here we describe a rodent model for the study of urinary catheter-associated Candida … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 65 publications
(95 reference statements)
0
39
0
Order By: Relevance
“…Using the XTT [2,3-bis-(2-methoxy-4-nitro-5-sulfophenyl)-2H-tetrazolium-5-carboxianilide] reduction assay, Uppuluri et al (204) demonstrated that biofilms formed in SU medium were as metabolically active as those grown in RPMI 1640 medium, although in SU medium, the final concentration of cells was lower, the hyphae were shorter, the biofilm architecture was less complex, and the expression of select filamentation-associated genes (EFG1, ALS3, and HWP1) was reduced. As is the case for the intravenous catheter model, the urinary catheter model developed by Andes and coworkers (188,203,205,206) is extremely effective for studying urinary catheter infections. In a subcutaneous model, van Dijck and coworkers (207,208) seeded pieces of catheter with implanted C. albicans yeast cells subcutaneously in the back of a mouse (Fig.…”
Section: Other Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the XTT [2,3-bis-(2-methoxy-4-nitro-5-sulfophenyl)-2H-tetrazolium-5-carboxianilide] reduction assay, Uppuluri et al (204) demonstrated that biofilms formed in SU medium were as metabolically active as those grown in RPMI 1640 medium, although in SU medium, the final concentration of cells was lower, the hyphae were shorter, the biofilm architecture was less complex, and the expression of select filamentation-associated genes (EFG1, ALS3, and HWP1) was reduced. As is the case for the intravenous catheter model, the urinary catheter model developed by Andes and coworkers (188,203,205,206) is extremely effective for studying urinary catheter infections. In a subcutaneous model, van Dijck and coworkers (207,208) seeded pieces of catheter with implanted C. albicans yeast cells subcutaneously in the back of a mouse (Fig.…”
Section: Other Modelsmentioning
confidence: 99%
“…This model has also not been adopted generally, for the same reasons noted for the model of Andes et al (36), but it also appears to be an excellent one for studying catheter infections. A urinary catheter model, also developed by Andes and coworkers (203) and diagrammed in Fig. 5B, involved inserting a silicone catheter into the urethra of an immunosuppressed rat treated with antibiotics ( Fig.…”
Section: Other Modelsmentioning
confidence: 99%
“…A rat urinary catheter biofilm model was used as a model to mirror indwelling urinary catheter infections in patients (14). Briefly, animals received a single dose of cortisone acetate (250 mg/kg) subcutaneously.…”
Section: Methodsmentioning
confidence: 99%
“…For examination of the extracellular matrix composition of in vivo Candida biofilms, we chose to include three rat models of C. albicans biofilm infection that closely mimic common clinical scenarios (14)(15)(16). Mature biofilms formed on the surfaces of these devices, including a vascular catheter, urinary catheter, and denture device, contained abundant extracellular matrix material as visualized by scanning electron microscopy (Fig.…”
Section: Imaging Of C Albicans In Vivo In Vitro and Ex Vivo Biofilmsmentioning
confidence: 99%
See 1 more Smart Citation